Kajian Stilistika Pada Puisi ”Aku” Karya Chairil Anwar dan Implementasinya Terhadap Pendidikan Karakter Siswa - Sri Silfiani; Diena San Fauziya (Simpati, 2024)
This research aims to describe the stylistic studies contained in the poem "Aku" by Chairil Anwar, as well as its implementation in student character education. The method used in this research is descriptive qualitative with stylistic studies. The results of the analysis show that through this approach, the poem "Aku" by Chairil Anwar is considered an effective tool for developing student character. The implementation of holistic and contextual character education can help students understand the beauty of literary works in Indonesia and internalize the important values ​​contained in poetry, then apply them in everyday life.